Finance Cash Management Pada PT. MAP Aktif Adiperkasa, Tbk - Keren Kartini Juanda; Arwina Karmudiandri; Julisar Surjadi; Tjhai Fung Jin (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This internship was held at PT MAP Aktif Adiperkasa, Tbk, a retail company of sports, toys, and lifestyle products. The work assigned to the author relates to internal payments such as processing reimbursement claims, petty cash reimbursement, advance, and advertisement tax payments. While processing reimbursement claims, the author encountered various problems and then decided to make a guide for processing reimbursement claims and identify reimbursement claim system as an innovation project. The author gained a lot of experience and knowledge and could complete projects on time. The limitation of the reimbursement claim system allows the requestor to attach the invoice for one of the expense types. The system should be improved by not allowing the requestor to submit the form if the invoice has not been completely attached to each expense type.